Transformasi Digital Inovasi Pelayanan Publik Aplikasi JAKI dalam Mewujudkan Smart Governance di DKI Jakarta - Sinta Dewi, Sang Ayu Nyoman; Adi Sastra Wijaya , Komang; Dharmanu Yudartha, I Putu; Savitri, Renny (Badan Penerbitan Jurnal (BPJ) FIA-UB, 2023)
The JAKI (Jakarta Kini) application as a form of realization of smart governance during its management experienced several problems including a decrease in the number of application users, user privacy was not fulfilled, and the integration concept was not yet optimal. This research aims to analyze and describe the implementation of smart governance and identify inhibiting and driving factors in the JAKI (Jakarta Kini) application. The type of research used is descriptive qualitative. Primary data sources were obtained from interviews and secondary data from articles, books and previous research. The data analysis technique uses the Miles and Huberman model. The research results show that the digital innovation transformation of the JAKI (Jakarta Kini) application in realizing smart governance has been realized by the DKI Jakarta government. In the dimensions of leadership, cooperation or partnership, accountability and transparency have been fulfilled. However, the dimensions of participation, communication, data exchange, services and application integration have not been fulfilled due to the management of quite a lot of Regional Apparatus data and the lack of even socialization by the management, namely the Jakarta Smart City Regional Public Service Agency.